Towards comprehensive and disciplined change management strategy in agile transformation process. - Gandomani, Taghi Javdani; Zulzalil, Hazura; Abd Ghani, Abdul Azim; Md. Sultan, Abu Bakar (Maxwell Science Publication, 2013)
Moving to agile through a well-defined strategy and framework is essential and this socio-technical process should be studied in deep. Advantages and earned values of agile approach in software industry motivate a lot of companies to try to use agile methods in their software product lines. Transformation process to agile methods is not easy and because of its nature, takes a long time. Since agile transformation needs organizational mutation, companies are faced with many challenges during this process. While several studies have been conducted for how to use agile methods, some other studies have focused on finding obstacles in agile adoption process. However, previous studies are valuable, but each of them has focused the change process from a particular perspective. In this study we discuss the dimensions of agile transformation process from a wider perspective. We will show that focusing on agile adoption is not the only master key for success in agile transformation process and we need to define an agile change management strategy for this organizational metamorphosis. This strategy should consider all aspects of changing approach and is underpinning of achievement in agile transformation process through substantive transformation experiences.